The prospects of natural fiber composites: A brief review - Sivasubramanian Palanisamy; Kavimani Vijayananth; Thulasi Mani Murugesan; Murugesan Palaniappan; Carlo Santulli (International Journal of Lightweight Materials and Manufacture, 2024)
This research explores natural fiber composites (NFCs) as alternatives to traditional materials such as fiberglass. By examining fibers like abaca, bamboo, banana, coir, flax, hemp, jute, kenaf, pineapple leaf (PALF), sisal, and others, we emphasize their lower weight, cost-effectiveness, competitive mechanical properties, commendable specific strength, and potential for biodegradability. NFCs offer practical and eco-friendly substitutes for conventional composite fibers in industries like construction, automotive, and packaging. The article provides a brief overview of NFCs, covering their chemical, physical, and mechanical characteristics, and highlights diverse applications. The comparative analysis underscores the potential of natural fibers as sustainable choices in various industries.